Urban wetlands as a potential habitat for an endangered aquatic plant, Isoetes sinensis - Wang, Yue; Fukuda, Hiroatsu; Zhang, Pengchong; Wang, Ting; Yang, Guofu; Gao, Weijun; Lu, Yijun (Global ecology and conservation, 2022)
Urban wetlands play an important role in the urban ecological environment. Due to their special habitat characteristics, urban wetlands can serve as micro refuges for endangered plants. This study takes Isoetes sinensis as a case study to explore the feasibility of introducing endangered plants into urban wetlands to identify potential habitats through field studies, eco-physiological experiments, and urban wetland surveys in the central district of Hangzhou, China. The study demonstrates that I. sinensis can survive in habitats with a water depth less than 15 cm, a water velocity less than 0.04 m/s, and an ammonium-nitrogen content in water less than 0.5 mg/L. On this basis, 1.75% of the wetland (145.38 ha) in the central district in Hangzhou can serve as wetland habitats for I. sinensis. Moreover, other potential habitats for I. sinensis will be available following further improvement of environmental conditions in urban wetlands. Planting I. sinensis in urban wetlands is an effective step to assist in the protection of this species. However, it should be noted that there are some uncertainties related to successful reintroducing I. sinensis into urban wetlands, such as the appearance that like weeds, the poor resistance to pesticides and the changes of urban wetland environment.